2018
DOI: 10.1111/ffe.12777
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic cryogenic pretreatments influencing the mechanical properties of a bulk glassy Zr‐based alloy

Abstract: In this study, cryogenic thermal cycling was applied to bulk glassy Zr52.5Cu17.9Al10Ni14.6Ti5 (Vitreloy 105) bending samples. After that, significantly improved plasticity and better fatigue properties at three‐point bending as well as higher impact toughness were measured in dependence of the duration and the cooling rate of the thermal cycling process. This improved material behaviour is caused by reinforced shear banding, visible in scanning electron microscopy at the side faces of the specimens after fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Remarkably, recent experimental studies on metallic glasses have demonstrated that cryogenic thermal cycling can induce rejuvenation that leads to less relaxed states of higher energy and improved plasticity [4][5][6][7][8]. It was argued that atomic-scale structural rejuvenation upon thermal cycling might be caused by internal stresses that arise due to spatially heterogeneous thermal expansion of the amorphous material [9].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, recent experimental studies on metallic glasses have demonstrated that cryogenic thermal cycling can induce rejuvenation that leads to less relaxed states of higher energy and improved plasticity [4][5][6][7][8]. It was argued that atomic-scale structural rejuvenation upon thermal cycling might be caused by internal stresses that arise due to spatially heterogeneous thermal expansion of the amorphous material [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of methods were proposed to enhance plasticity of metallic glasses, such as addition of chemical heterogeneities [5,6] or a soft second phase [7]. A less intrusive way to tune the amorphous structure is to apply cryogenic thermal cycling that can induce rejuvenation due to heterogeneity in the local thermal expansion and therefore improve plasticity [8][9][10][11][12][13]. Using atomistic simulations, it was recently shown that internal stresses due to thermal expansion can in principle trigger a plastic event in sufficiently large systems [14].…”
Section: Introductionmentioning
confidence: 99%
“…The long‐range disordered structure in the molten liquid will be preserved, and accordingly, no microdefects like dislocations and grain boundaries can be formed 1 . This unique structure renders that the highly strain‐localized shear bands become the main mechanism dominating the plastic deformation and also play a key role in the fatigue crack initiation and propagation in MGs 2–4 . The fast propagation and failure of the individual shear band usually deteriorate the mechanical properties such as the nearly zero global tensile plasticity and low fatigue resistance, which severely restricts the potential applications as structural materials 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…1 This unique structure renders that the highly strain-localized shear bands become the main mechanism dominating the plastic deformation and also play a key role in the fatigue crack initiation and propagation in MGs. [2][3][4] The fast propagation and failure of the individual shear band usually deteriorate the mechanical properties such as the nearly zero global tensile plasticity and low fatigue resistance, which severely restricts the potential applications as structural materials. [5][6][7] One intrinsic method of overcoming these problems is to develop the MG composites (MGCs) by introducing a "microstructure" (such as crystalline dendrites, particles, and fibers) into the MG matrix, which can interact with the shear banding behaviors and constrain the propagation of the individual shear band.…”
Section: Introductionmentioning
confidence: 99%